Developing and validating a genre awareness questionnaire for writing scientific reports - Pun, Jack; Cheung, Kason Ka Ching (Frontiers in Psychology, 2023)
Current scholarship on language awareness focuses on learners’ noticing of forms and functions of language. In writing scientific reports, learners need to be aware of the Introduction, Method, Results and Discussion (IMRD) genres. While scholarship explores students’ language awareness in writing genres for scientific reports, there is limited quantitative instrument for researchers to measure students’ language awareness in these four genres of writing scientific articles. This study investigates the structure of factors of a Language Awareness of Genres in Scientific Writing Questionnaire that measures students’ awareness of IMRD genres for L2 bilingual secondary school students in Hong Kong (N=234). Content validity and construct validity was used. The results show that this instrument is reliability for researchers and teachers to understand the effectiveness of specific genre-based intervention on genre awareness.